Estimation of the glutathione system parameters depending on the variant of the disease course in patients with newly diagnosed pulmonary tuberculosis at coinfection tuberculosis/HIV - R. M. Yasinskiy (Zaporožskij Medicinskij Žurnal)
The aim was to estimate the thiol-disulfide compounds depending on the variant of disease course in tuberculosis/HIV co-infected patients with newly diagnosed tuberculosis (NDT/HIV). Materials and methods. The study involved 54 patients with NDT/HIV, who were treated in the clinic of Zaporizhzhia regional clinical tuberculosis dispensary during 2010 – 2014 (average age 37,8 ± 1,2 y), 41 (75,9%) men, 13 (24,1%) women. Focal tuberculosis was diagnosed in 5 cases (9,3%), infiltrative – in 25 (46,3%) cases, disseminated – in 24 (44,4%) cases. The control group included 32 healthy individuals – blood donors (average age 35,9 ± 2,5 y), 22 (68,7%) men, 10 women (31,3%). Patients depending on the results of the treatment were retrospectively were divided into 3 groups: 1 – 15 patients with positive dynamics, 2 - with progressive disease course without systemic inflammatory response syndrome (n=13), 3 –with progressive disease course with SIRS (n=26).